2019
DOI: 10.33594/000000128
|View full text |Cite
|
Sign up to set email alerts
|

Dual and Opposing Regulation of MMP1 and MMP13 by Both Arms of miR-675 in Human Articular Chondrocytes

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Of all differentially expressed miRNA sequences 40 were 3p strands, 36 were 5p strands and 24 of the 76 sequences were isomiRs. Several of the canonical miRNAs upregulated in ACs, such as miR-675-3p and 5p, miR-335-5p, miR-582-5p and 3p, miR-9-5p, miR-136-3p and miR 495-3p are known to be involved in cartilage biogenesis and disease ( Tomé et al, 2011 ; Díaz-Prado et al, 2012 ; Chen et al, 2017 ; Chen et al, 2018 ; Zhong G. et al, 2019 ; Chen et al, 2019 ; Seidl and Murphy, 2019 ; Wang et al, 2019 ; Chen et al, 2020 ; Shen et al, 2020 ; Zhang et al, 2021 ). Of the highest differentially expressed canonical miRNAs in MSCs miR-10a-5p, miR-181b, miR-181a, miR-135b-5p and miR-218-5p are known to be involved in osteogenesis, cartilage hypertrophy and degeneration and OA ( Bhushan et al, 2013 ; Song et al, 2013 ; Gabler et al, 2015 ; Nakamura et al, 2016 ; Lu et al, 2017 ; Ma et al, 2019 ; Yin et al, 2019 ; Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all differentially expressed miRNA sequences 40 were 3p strands, 36 were 5p strands and 24 of the 76 sequences were isomiRs. Several of the canonical miRNAs upregulated in ACs, such as miR-675-3p and 5p, miR-335-5p, miR-582-5p and 3p, miR-9-5p, miR-136-3p and miR 495-3p are known to be involved in cartilage biogenesis and disease ( Tomé et al, 2011 ; Díaz-Prado et al, 2012 ; Chen et al, 2017 ; Chen et al, 2018 ; Zhong G. et al, 2019 ; Chen et al, 2019 ; Seidl and Murphy, 2019 ; Wang et al, 2019 ; Chen et al, 2020 ; Shen et al, 2020 ; Zhang et al, 2021 ). Of the highest differentially expressed canonical miRNAs in MSCs miR-10a-5p, miR-181b, miR-181a, miR-135b-5p and miR-218-5p are known to be involved in osteogenesis, cartilage hypertrophy and degeneration and OA ( Bhushan et al, 2013 ; Song et al, 2013 ; Gabler et al, 2015 ; Nakamura et al, 2016 ; Lu et al, 2017 ; Ma et al, 2019 ; Yin et al, 2019 ; Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance overexpression of miR-675-3p has been found to inhibit apoptosis and cartilage matrix degradation and promote cell proliferation in human chondrocytes ( Shen et al, 2020 ). The 3′ arm of miR-675 was found to be the only functional arm of miR-675 in ACs, and was found to downregulate cartilage degrading enzymes matrix metalloprotein 1 (MMP1) and MMP13 ( Seidl and Murphy, 2019 ). MiR-335-5p has been shown to inhibit adipogenic and osteogenic differentiation of hMSCs ( Tomé et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-134 was found to regulate MMP3 expression by Chen [36]. Similarly, Seidl CI et al [37] found that miR-675 could regulate MMP13 expression, but it has also been found that miR-411 could also regulate MMP13 expression by expression to regulate tissue repair [38].…”
Section: Resultsmentioning
confidence: 99%
“…IL21 was found to suppress HC-a chondrocyte proliferation, promote apoptosis, and downregulate miR-361-5p. The restoration of HC-a cell functions was noted with increased miR-361-5p, implicating MAP3K9 as a target gene, and revealing a role for miR-361-5p in regulating MMP1, a collagen-degrading enzyme [ 32 ]. The ERK1/2/NF-κB signaling pathway’s involvement in MMP expression was confirmed using specific agonists.…”
Section: Discussionmentioning
confidence: 99%